Governing information technology (IT) investment: A contingency perspective on organization's IT investment goals. Issue 1 (February 2022) - Ali, Syaiful; Green, Peter; Robb, Alastair; Masli, Adi
Using contingency theory, we argue that there is not a uniform approach for companies to govern information technology (IT) investments. Rather, the level of governance over IT investments is contingent upon the organization's goals for its IT investments. We find that Australian organizations with both operation- and market-focused IT investment goals (i.e. dual-focused IT goals) demonstrate higher IT investment governance (ITIG) levels than those with less focused IT goals. We also document that dual-IT-focused firms that do not implement high levels of ITIG underperform. Our study informs business executives, boards of directors, and other practitioners interested in governance implementations over IT investments. JEL Classification:M1